Epidemiology of measles cases and phylogenetic analysis of the virus circulated in the Federation of Bosnia and Herzegovina during 2018: implications for elimination efforts - Irma Salimović-Bešić; Sanjin Musa; Nijaz Tihić; Jurica Arapović; Mirsada Hukić; Mensura Šeremet; Edina Zahirović; Suzana Arapčić; Amela Dedeić-Ljubović (Medicinski glasnik, 2019)
Aim: To present combined measles cases data and phylogenetic analysis of the virus circulated in 2018 in the Federation of Bosnia and Herzegovina (FB&H, the entity of Bosnia and Herzegovina), in order to analyse endemic transmission patterns of circulating strains and its implications for elimination efforts. Methods: The data were derived from epidemiological case investigations and laboratory diagnoses based on serology, molecular detection and genotyping of the measles virus. Results: During 2018 16 measles cases were reported in FB&H, of which five were classified as laboratory confirmed cases, one was an epidemiologically linked case and 10 were clinically compatible cases. Among them 12 (75.00%) cases were unvaccinated or had unknown vaccination status. The most affected population was up to 14 years of age (13/16; 81.25%). None of the cases was fully vaccinated. Viruses of other genetic lineages had been introduced in FB&H in the recent period. Two virus lineages of genotype B3 were identified. Phylogenetic analysis indicated the presence of a unique sequence of measles B3 virus in FB&H (Sarajevo). Conclusion: Further strengthening of measles surveillance system and renewed efforts to increase vaccination levels are necessary to prevent disease and for elimination setting.
Keywords: genotype; measles virus; phylogeny; vaccination; virus diseases